Josep Sanxo i Sanxo, Josep & F. Xavier Martín Martínez (ed.), «Diari (1824-1844)», Barcelona, Institut Menorquí d’Estudis / Publicacions de l’Abadia de Montserrat, 2018, 269 p. - Martínez Mayor, Carlos (Caplletra. Revista Internacional de Filologia, 2019)
Ressenya sobre el llibre de Josep Sanxo i Sanxo, Josep & F. Xavier Martín Martínez (ed.), Diari (1824-1844), Barcelona, Institut Menorquí d’Estudis / Publicacions de l’Abadia de Montserrat, 2018, 269 p., ISBN 978-84-9191-007-7.